2019
DOI: 10.1002/jhet.3856
|View full text |Cite
|
Sign up to set email alerts
|

Green and ecofriendly synthesis of indole‐condensed benzimidazole chalcones in water and their antimicrobial evaluations

Abstract: An ecofriendly synthesis of novel benzimidazole‐substituted indole derivatives catalyzed by ZnO nanoparticles has been developed from simple condensation of acetyl benzimidazole and indole‐3‐carbaldehyde followed by Michael addition of indoles. This ZnO Nano particles (NP)‐catalyzed reaction has been carried out using both step‐wise and one‐pot methods, and both these methods provide excellent yield of product and less reaction time in water. All the synthesized compounds were characterized by Infrared spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Several solvents, catalysts, and temperatures were evaluated to tune the best conditions to obtain the desired compounds with good yields, as reported in Figure 10B . The chalcone is formed as the first step of the proposed mechanism and then it reacts as an intermediate with the indole-derivative to produce the final compounds ( Dasari et al, 2020 ).…”
Section: Tools and Strategies For Improving The Efficiency Of Chalcon...mentioning
confidence: 99%
“…Several solvents, catalysts, and temperatures were evaluated to tune the best conditions to obtain the desired compounds with good yields, as reported in Figure 10B . The chalcone is formed as the first step of the proposed mechanism and then it reacts as an intermediate with the indole-derivative to produce the final compounds ( Dasari et al, 2020 ).…”
Section: Tools and Strategies For Improving The Efficiency Of Chalcon...mentioning
confidence: 99%
“…[ 73 ] The bisindole–benzimidazole hybrids 29 (MIC: 28–400 μg/ml) showed a weak‐to‐moderate activity against E. coli , P. vulgaris , S. typhimurium , K. pneumoniae , and S. aureus , and the SAR demonstrated that substituents on the indole and benzimidazole moieties had little impact on the activity. [ 74 ]…”
Section: Indole/isatin–azole Hybridsmentioning
confidence: 99%
“…They are well known as bioactive compounds, fluorescent materials, and reaction intermediates (Figure 1). Chalcones have been employed in medicinal chemistry as antioxidants [4], antiinflammatory [5], anticancer [6], antidiabetic [7], antiviral [8], antimalarial [9], antimicrobial [10,11], etc. Metochalcone (cholerectic drug) and sofalcone (antiulcer and mucoprotective drug) are the two examples of chalcone-containing drugs [12,13].…”
Section: Introductionmentioning
confidence: 99%